Improving the Ability to Observe, Identify and Define Variables Through Comic-Assisted Inquiry Learning Model - Husna, Wardatul; Evendi, Evendi; Syukri*, Muhammad; Elisa, Elisa; Herliana, Fitria; Mohtar, Lilia Ellany; Putri, Elva Sesioria (Jurnal Pendidikan Sains Indonesia, 2024)
This research is motivated by students' science process skills which are still in the low category. Based on the initial observations made there were students who still had difficulty in conducting experiments. This research aims to determine the increase in the ability to observe, identify and define variables through the comic-assisted inquiry learning model. This research was conducted on class XI MIPA 2 students at SMAN 2 Banda Aceh involving 32 students. The research design used in this study isone grup pretest-posttest design. Data collection techniques through tests (pretest andposttest) and student response. The pretest and posttest questions in this research were prepared referring to three indicators of science process skills, namely, observing, identifying and defining variables. After the data is collected, the data is analyzed using the gain test. The results of the research showed that there was an increase in students' science process skills in the aspect of observing by 0.54 in the medium category, identifying by 0.68 in the medium category and defining variables by 0.72 in the high category. Based on the results of this research, it can be concluded that the ability to observe, identify and define variables can be improved through comic-assisted inquiry learning